Effects of probiotic Bacillus subtilis and B. licheniformis on water quality, growth, physiology, gene expression, and disease resistance in Sparus aurata fingerlings - Nassar, Safaa E.; Abd Al-Kareem, Omayma M.; El Araby, Rania El Sayed; Mahsoub, Fatma; El-Haroun, Ehab; Osailan, Raha; Eissa, Moaheda E.H.; Eissa, El-Sayed Hemdan; Ahmed, Norhan H. (Frontiers in Marine Science, 2025)
This study evaluated the effects of a probiotic blend of Bacillus subtilis and Bacillus licheniformis, administered as a water additive, on the growth performance, feed efficiency, body composition, blood biochemistry, histology, gene expression, and resistance to Vibrio parahaemolyticus infection in Sparus aurata fingerlings. A total of 240 healthy fingerlings (6.10 ± 0.06 g) were distributed into 12 tanks (3 tanks per group), with 20 fish per tank. Over a period of 10 weeks, the fish were exposed to four treatments with increasing probiotic concentrations (0, 0.01, 0.02, and 0.03 g/m³), designated as Control, BSL1, BSL2, and BSL3, respectively. The water additives of BSL significantly increased the dissolved oxygen (mg/L) in a dose-dependent manner, while the values of TAN were significantly reduced by increasing the levels of BSL in the water. The NH3 levels were the lowest in BSL2 and BSL3 compared to other groups; however, BSL1 was lower than the control group. The BSL3 group exhibited higher growth performance (final body weight, BWG, survival rate) compared to the other groups (P < 0.05). Adding BSL significantly improved the crude protein and ash content in S. aurata, while it significantly reduced the lipid content (P<0.05). BSL also significantly improved blood hematology parameters (PCV, RBCs, and Hb) and immune responses (phagocytic activity, phagocytic index, lysozyme activity, IgM, total Ig, and WBCs) in a dose-dependent manner (P<0.05) compared to the control group. Blood biochemical parameters (Total protein, albumin, globulin, and glucose), digestive enzymes (amylase and lipase) and antioxidant status (TAC, SOD, CAT) were significantly increased in a dose-dependent manner with increasing levels of probiotic in the water (P<0.05). Liver enzymes and MDA were significantly decreased by BSL-water addition (P<0.05). BSL enhanced the intestinal structure integrity of Sparus aurata. The addition of B. subtilis and B. licheniformis probiotics significantly improved the growth factors (IGF-1, IGF-2, and GHR) and immune-related genes (TNF-α, IL-1β, and IL-10) compared to the control group (P<0.05) in a dose-dependent manner. Importantly, probiotic-treated fish exhibited increased resistance to V. parahaemolyticus infection. These findings suggest that water addition of Bacillus subtilis and Bacillus licheniformis probiotics at a concentration of 0.2-0.3g/m3 improved the growth and overall health of Sparus aurata by regulating the immune responses and antioxidant status.